The information literacy framework case studies of successful implementation - Julien, Heidi E. (Heidi Elizabeth), 1960-; Gross, Melissa; Latham, Don, 1959- (Association for Library and Information Science Education series., 2020)
"This edited book helps demystify how to incorporate ACRL's Framework for Information Literacy for Higher Education into information literacy instruction in higher education as well as how to teach the new Framework to pre-service librarians as part of their professional preparation"--